Pendampingan Pengelolaan Media Sosial Bagi Pelaku Usaha UMKM Tanaman Hias Bonsai: Indonesia - Johansyach, Muhammad Wildan; Abadi, Totok Wahyu; febriana, poppy (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
The Community Service Program (Abdimas) is an effort to resolve problems related to owners of Micro, Small and Medium Enterprises (MSME) Bonsai Letters in Gempol, Pasuruan. The problem is that these business actors do not understand social media management. Therefore, social media is important for business actors in introducing products efficiently and marketing on social media which previously only used conventional approaches. The aim of this research is assistance provided to business actors so that they can market their ornamental plants at a more sophisticated, modern level and with a wider reach with the existence of social media platforms. The methods for the program implementation stages in this research are observation and interviews, idea planning, activity processes, mentoring and activity evaluation. The activity will be held twice a week, namely from Sunday, 18 and 25 June 2023 at 09.00 – 13.00 WIB at the Gempol bonsai script stand, Pasuruan. The results of the activity are that MSME business actors have understood media management as a forum for selling/marketing products, arranging sales stalls, and how to create a logo as an MSME identity.